Health care provider's experience and perspective of cervical cancer screening in Singapore: A qualitative study - Chua, Brandon Wen Bing; Neo, Pearlyn; Ma, Viva Yan; Lim, Li Min; Ng, Joseph Soon Yau; Wee, Hwee Lin (Frontiers in Public Health, 2022)
Background: In Singapore, the current cervical cancer screening (CCS) coverage rate of 48% falls below the national target of 70%. Health care providers (HCPs) play a critical role in promoting CCS uptake. However, there is limited understanding of the perspectives of HCPs regarding CCS. Hence, we aimed to understand the challenges encountered by HCPs delivering CCS in different care settings in the Singapore health system. We also aimed to explore perspectives on newer features of CCS such as self-sampling and HPV genotyping. Methods: Physicians, nurses, program administrators and laboratory technicians involved with CCS were invited for a one-on-one semi-structured interview conducted over Zoom between May to August 2021. The interviews were transcribed and analyzed using thematic analysis. Results: Eighteen HCPs from 12 institutions were interviewed. Most participants were women (61.1%) and worked in public health institutions (72.2%). Nine key themes were identified and organized into four categories: (1) patient factors, (2) HCP factors, (3) health system factors and (4) health promotion factors. Key themes commonly highlighted by study participants were related to patients’ preferences and acceptance for screening, the processes of delivering CCS, the national priority for cervical cancer and the effectiveness of existing health promotion efforts. Self-sampling was viewed favorably to increase CCS uptake, while primary HPV screening with HPV partial genotyping had higher sensitivities to detect pre-cancers and cancers compared to cytology. Extended HPV genotyping beyond HPV16/18 could play an important role in CCS with increasing HPV vaccination coverage, as well as in the management of persistent HPV infection. Conclusion: In Singapore, HCPs face multiple challenges for CCS in practice. Insights from this study are directly relevant to, and useful for developing policies around national CCS programs and treatment guidelines.